Novel approaches to tackling antimicrobial resistance: the design, synthesis and evaluation of quorum sensing inhibitors in Pseudomonas aeruginosa - Grossman, Scott (2022)
The bacterium Pseudomonas aeruginosa is a nosocomial pathogen, which causes infection in immunocompromised patients. Its high levels of antibiotic resistance make P. aeruginosa infections difficult to treat, and examples of pan-resistant P. aeruginosa have been observed. P. aeruginosa contains three intertwined quorum sensing (QS) systems, which aid in the onset and continuation of infection through community-wide communication. The las, rhl and pqs systems, which are controlled by their respective transcriptional regulators LasR, RhlR and PqsR, regulate the production and detection of signal molecules, as well as other virulence factors such as the toxins pyocyanin and HCN. Therefore, inhibition of QS circuits can lead to therapeutic benefits and shows promise as a method of decreasing the occurrence of drug-resistant microorganisms.